2019
DOI: 10.30728/boron.515517
|View full text |Cite
|
Sign up to set email alerts
|

Sytnhesis of Organoboron Amide-Ester Branched Derivatives of Poly(Itaconic Anhydride-alt-2-Vinyl-1,3-Dioxolane) and Cancer Cells Interaction Studies

Abstract: New organaboron amide-ester branched derivatives of poly(itaconic anhydridealt-2-vinyl-1,3-dioxolane) are synthesized by amidolysis and grafting reactions, respectively. The structure and composition of the synthesized compounds are characterized by FTIR-ATR (Fourier Transform-Infrared-Attenuated Total Reflection) and 1 H (13 C) NMR (Nuclear Magnetic Resonance) spectroscopy. These novel functionalized boron containing biopolymers are interacted with HeLa (human cervix carcinoma cell) cancer cells and L929 Fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Replacement of covalent carbon‐carbon bonds with boron‐nitrogen bonds has in many cases provided compounds with significantly improved biological and electronic properties. Moreover, the boron centre can be converted from neutral trigonal planar (sp 2 ) to tetrahedral (sp 3 ) hybridization under proper physiological conditions to form strong interactions with the receptor (Özçayan, 2019). Previous studies on the 2,1‐borazaronaphthalenes, for example, have demonstrated strong correlation of their biological properties in vitro as inhibitors of phosphodiesterase 10A (PDE10A; Vlasceanu et al., 2015) and β2 receptor (Rombouts et al., 2015) compared to the reference standards used for the assays.…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of covalent carbon‐carbon bonds with boron‐nitrogen bonds has in many cases provided compounds with significantly improved biological and electronic properties. Moreover, the boron centre can be converted from neutral trigonal planar (sp 2 ) to tetrahedral (sp 3 ) hybridization under proper physiological conditions to form strong interactions with the receptor (Özçayan, 2019). Previous studies on the 2,1‐borazaronaphthalenes, for example, have demonstrated strong correlation of their biological properties in vitro as inhibitors of phosphodiesterase 10A (PDE10A; Vlasceanu et al., 2015) and β2 receptor (Rombouts et al., 2015) compared to the reference standards used for the assays.…”
Section: Introductionmentioning
confidence: 99%